2019
DOI: 10.1186/s13065-019-0573-z
|View full text |Cite
|
Sign up to set email alerts
|

A new insight of structures, bonding and electronic properties for 6-mercaptopurine and Ag8 clusters configurations: a theoretical perspective

Abstract: Background Many reports have also shown that the silver nanoparticles can effectively increase the anticancer drug activity and intensely enhance the drug curative effect. The adsorption of 6MP on nanomaterials has received a lot of attentions because of the drug coordination to its chemotherapeutic activity. The geometrical structures, chemical bonds, molecular orbital properties as well as density of states for the configurations were analyzed to deeply understand the interactions between the 6M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The Au 20 tetrahedron is also well-known as an outstanding indicator in cluster science for its exceptional stability and peculiar 20-electron superatom shell structure [62,63]. Regarding the molecular structure of a 6MP drug, out of several stable configurations [64,65], two planar tautomers-6MP-7 and 6MP-9, presented in Figure 2tend to dominate its ground state population with a large quantity in both the gas phase and aqueous environments, as reported in recent literature [48,64,66]. In a vacuum, 6MP-7 lies 3 kcal/mol above 6MP-9, but this energy difference is significantly reduced to~1 kcal/mol in a water solution (PBE/cc-pVTZ value).…”
Section: Structures and Energeticssupporting
confidence: 62%
See 1 more Smart Citation
“…The Au 20 tetrahedron is also well-known as an outstanding indicator in cluster science for its exceptional stability and peculiar 20-electron superatom shell structure [62,63]. Regarding the molecular structure of a 6MP drug, out of several stable configurations [64,65], two planar tautomers-6MP-7 and 6MP-9, presented in Figure 2tend to dominate its ground state population with a large quantity in both the gas phase and aqueous environments, as reported in recent literature [48,64,66]. In a vacuum, 6MP-7 lies 3 kcal/mol above 6MP-9, but this energy difference is significantly reduced to~1 kcal/mol in a water solution (PBE/cc-pVTZ value).…”
Section: Structures and Energeticssupporting
confidence: 62%
“…Rashidpour et al [47] analyzed the adsorption of 6MP on an Au 10 surface and found that the conjugation is energetically preferred via the S and S-N sites of the drug molecule. Ren and co-workers [48] also investigated the structures, bonding features, and stability of the complexes of 6MP with an Ag 8 cluster by means of DFT (B3LYP) calculations. In a recent study [49] we elucidated the binding mechanism of both 6-mercaptopurine and 6-thioguanine to the Au 6 and Au 8 clusters.…”
Section: Introductionmentioning
confidence: 99%